On the Ishikawa iteration processes for multivalued mappings in some [InlineEquation not available: see fulltext.] spaces - Panyanak B. (Springer Publishing Company, 2015)
© 2014, Panyanak; licensee Springer. The purpose of this paper is to prove the strong convergence of the Ishikawa iteration processes for some generalized multivalued nonexpansive mappings in the framework of CAT(1) spaces. Our results extend the corresponding results given by Shahzad and Zegeye (Nonlinear Anal. 71:838-844, 2009), Puttasontiphot (Appl. Math. Sci. 4:3005-3018, 2010), Song and Cho (Bull. Korean Math. Soc. 48:575-584, 2011) and many others.